2018
DOI: 10.3390/coatings8040150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Annealing on Residual Stress in Ta2O5 Films Deposited by Dual Ion Beam Sputtering

Abstract: Optical coatings deposited by the dual ion beam sputtering (DIBS) method usually show high compressive stress, which results in severe wavefront deformation of optical elements. Annealing post-treatment has been widely used to control the residual stress of optical coatings. However, the effect of annealing on the stress of Ta 2 O 5 films deposited by the IBS method has not been reported in detail. In this study, different thicknesses of Ta 2 O 5 films were deposited by IBS and annealed at different temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…2dsinθ=nλ ……. (6) Where d: the distance between levels, θ: diffraction angle, n: diffraction order, λ: X-ray wavelength. The parameters of the system are: source CuKα with radiation of wavelength λ=1.5406 Å.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2dsinθ=nλ ……. (6) Where d: the distance between levels, θ: diffraction angle, n: diffraction order, λ: X-ray wavelength. The parameters of the system are: source CuKα with radiation of wavelength λ=1.5406 Å.…”
Section: Methodsmentioning
confidence: 99%
“…An inert working gas, commonly Ar, is injected and acts as the medium for initiating and maintaining an electrical glow discharge [3]. In addition, prior research [Qipeng et al, 2018] has revealed that when deposited by magnetron sputtering at ambient temperature, the phase morphology of the as-deposited Tantalum films is amorphous. Hexagonal phases are unlikely to be representative of the crystalline phase obtained upon the application of a low thermal budget (<700ºC) and in the absence of a suitable substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ta 2 O 5 coatings are often used as high-performance materials in optical devices [ 20 ] due to their good optical properties, thermal stability [ 21 ] and chemical stability [ 22 ] in the visible and near-infrared regions, and high refractive index [ 23 ]. Ta 2 O 5 also has good mechanical properties such as wear resistance [ 24 ] and high hardness [ 25 ], and can be used as a protective coating.…”
Section: Introductionmentioning
confidence: 99%
“…Postprocessing can effectively improve the resistance to laser damage. In general, the post-processing methods of optical films include surface processing, [3,5,6] heat treatment, [7][8][9] post hot isostatic pressing, [9,10] etc. Among these methods, surface processing can increase LIDT through improving surface quality.…”
Section: Introductionmentioning
confidence: 99%